Effect of Ice Pack Application on Post-Extraction Pain and Swelling: A Ran domized Clinical Study (Academia Journal of Medicine, 2026)
Background: Post-extraction pain and facial swelling are common complications following dental extraction and can adversely affect patient comfort. Cryotherapy using ice pack application is a simple, economical, and non-invasive method used to reduce postoperative inflammation; however, its clinical effectiveness needs further evaluation. Aim: To evaluate the effect of ice pack application on postoperative pain and facial swelling following dental extraction. Materials and Methods: This randomized clinical study included 30 patients requiring routine dental extraction. The patients were randomly allocated into two groups with 15 patients in each group. Group I (Ice Pack Group) received extraoral ice pack application intermittently for 20 minutes during the first postoperative hour, while Group II (Control Group) received standard postoperative care without ice pack application. Postoperative pain was assessed using the Visual Analog Scale (VAS) at 6, 12, and 24 hours, and facial swelling was evaluated using standardized facial measurements at 24 and 48 hours post extraction. Statistical analysis was performed with the level of significance set at p < 0.05. Results: Group I demonstrated significantly lower mean pain scores and reduced facial swelling at all postoperative evaluation intervals compared to Group II (p < 0.05). The reduction in pain and swelling was more pronounced during the first 24 hours following extraction. Conclusion: Extraoral ice pack application is an effective adjunct in reducing postoperative pain and facial swelling following dental extraction. Its routine use can enhance patient comfort and postoperative recovery.
Keywords: Cryotherapy, Ice pack, Dental extraction, Postoperative pain, Facial swelling